AB0709 Association of tinu, nodal tuberculosis and renal amylosis. (23rd January 2014) - Baili, L.; Aydi, Z.; Dridi, M.; Ben Dhaou, B.; Kochbati, S.; Boussema, F.; Rokbani, L.
Abstract : Background: Tubulo-interstitial nephritis may be caused by drugs, infections or systemic diseases. However, the precise cause and etiology of the disease are unclear. Uveitis is a general terme of the inflammation of the iris and choroid. This ocular disorder is known to be complicated with several systemic disorders such as sarcoîdosis, Behecet's disease and toxoplasmosis. The association of tubulo-interstitial nephritis and uveitis (TINU) was first described in 1974. Subsequently, Dobrin et al reported two cases of interstitial nephritis complicated with anterior uveitis. Since then, this association has become known as Dubbin's syndrome. Objectives: We present a case of TINU associated with nodal tuberculosis and renal amylosis. Results: A 68-year-old woman with 4 months history of nodal tuberculosis diagnosed on histological study of cervical nodal biopsy was referred to our department for painful red eye and decreased vision in both eyes. Physical examination was unremarkable except for the bilateral red eye. Ophtalmological examination objective revealed bilateral non-granulomatous anterior uveitis. Laboratory finding was normal except for proteinuria (1g/24h). Urinary cytobacteriological exam showed aseptic leukocyturia . Antinuclear and antineutrophil cytoplasmic antibody test results were negative. Serological tests of infectious were negative. An ophthalmological examination revealed bilateral non-granulomatous anterior uveitis. Abdominal ultrasonography was normal. Histopathological examination of kidney biopsy showed amyloid deposits and tubulo-intersitial nephritis. Diagnosis of TINU was made. The patient was treated with antitubercular drugs. Eight months later, 24h urinary protein gets better and uveitis improved. Conclusions: TINU syndrome no longer appears to be so rare, but its mechanism remains unclear. It should be considered as differential diagnosis of unexplained tubule-interstitial nephritis especially in the presence of ocular finding. Disclosure of Interest: None Declared